How writing faculty write: strategies for process, product, and productivity - Tulley, Christine E., author; Utah State University Press, publisher (Colorado State University. Libraries, 2018)
Examines the writing processes of fifteen diverse writing faculty, revealing how each scholar develops an idea, conducts research, drafts and revises a manuscript, and pursues publication, through in-depth interviews--provided by publisher.
Introduction: Faculty Writing as a Research Area for Rhetoric and Composition -- 1. Cynthia Selfe -- 2. Joseph Harris -- 3. Dànielle DeVoss -- 4. Melanie Yergeau -- 5. Jessica Enoch -- 6. Jonathan Alexander -- 7. Kathleen Yancey -- 8. Chris Anson -- 9. Duane Roen -- 10. Cheryl Glenn -- 11. Malea Powell -- 12. Howard Tinberg -- 13. Thomas Rickert -- 14. Jacqueline Royster -- 15. Kristine Blair -- 16. Carving Out a Writing Life in the Discipline of Rhetoric and Composition: What We Can Learn from Writing Faculty -- Afterword -- Appendix: Sample Interview Questions
Keywords: Academic writing; Manuscript preparation (Authorship); College teachers -- Interviews; College teachers as authors